Kredit Rentenir dan Silaturahmi - Pratiwi, Novita Rahayu; Prajawati, Maretha Ika; S, Basir (Fakultas Ekonomi Universitas Samudra, 2021)
The study aims to analyze the meaning of debt according to the people of Kampung Kauman who prefer moneylenders than banks as their source of credit. This qualitative research uses a case study. Primary data were obtained through interviews with residents of Kampung Kauman, Pasrepan Village, Pasuruan Regency, East Java, which is located in an Islamic boarding school environment with a religious type of community. Secondary data in the form of details of the credit system to moneylenders. The sample used is saturated, i.e. all those who are credit members to loan sharks. Total informants numbered 21 of 30 households in Kauman Village. The results of this study indicate that the meaning of credit to loan sharks for the community in the study site environment is venture capital, a friendly place of association, mutual relief among credit members, and regarding usury laws on credit.